Response of GaN to energetic ion irradiation: conditions for ion track formation. (13th July 2015) - Karlušić, M; Kozubek, R; Lebius, H; Ban-d'Etat, B; Wilhelm, R A; Buljan, M; Siketić, Z; Scholz, F; Meisch, T; Jakšić, M; Bernstorff, S; Schleberger, M; et al.
Abstract: We investigated the response of wurzite GaN thin films to energetic ion irradiation. Both swift heavy ions (92 MeV Xe 23+, 23 MeV I 6+ ) and highly charged ions (100 keV Xe 40+ ) were used. After irradiation, the samples were investigated using atomic force microscopy, grazing incidence small angle x-ray scattering, Rutherford backscattering spectroscopy in channelling orientation and time of flight elastic recoil detection analysis. Only grazing incidence swift heavy ion irradiation induced changes on the surface of the GaN, when the appearance of nanoholes is accompanied by a notable loss of nitrogen. The results are discussed in the framework of the thermal spike model.